The Beginning of New Successful Year of the Journal of Dental Problem and Solutions - Vesna Ambarkova (Journal of Dental Problems and Solutions - Peertechz Publications, 2016)
Here we are, at the beginning of another year, at the beginning of another volume, but also at the beginning of the third year of the continuous publication of the Journal of Dental Problems and Solutions. Since 2014 until today, a total of 4 issues and 19 articles were published, by colleagues from different countries. It is not so much, but we must build tradition of stability and regularity in publishing. Until know, the journal has eighty members of the editorial board from all over the world. Keeping a scientific journal alive today is a difficult task because they are not popular as professional journals, they do not gain profit, but they help us scientists obtain aims that we have decided to pursue.